Prices for Crop and Livestock Cost-Return Budgets - Dhuyvetter, Kevin C.; O'Brien, Daniel M.; Tonsor, Glynn T. (My University, 2014)
A publication detailing wheat, corn, grain sorghum, and soybean price projections.
MF1013_2014-01
Keywords: MF1013; Economics; Crops; MF